2018
DOI: 10.1016/j.transproceed.2018.02.133
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Skin Diseases in Maintenance Hemodialysis

Abstract: The presented results prove the necessity of performing dermatological examinations on HD patients. Some dermatological skin lesions, if not diagnosed and treated, could progress to cancer after organ transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…This may be because this study had a much smaller sample size (n = 54). However, a recent study carried out by Ankudowicz et al [21] in 2018 found a prevalence more similar to that of our research (56.6% of nail pathology), although not as high since the patients were not kidney transplants but were undergoing hemodialysis treatment.…”
Section: Prevalence Of Skin and Nail Pathologysupporting
confidence: 84%
See 1 more Smart Citation
“…This may be because this study had a much smaller sample size (n = 54). However, a recent study carried out by Ankudowicz et al [21] in 2018 found a prevalence more similar to that of our research (56.6% of nail pathology), although not as high since the patients were not kidney transplants but were undergoing hemodialysis treatment.…”
Section: Prevalence Of Skin and Nail Pathologysupporting
confidence: 84%
“…The scientific evidence is ample in relation to the repercussions on the foot in subjects with ESRD, Diabetes Mellitus, and the elderly; however, there has not been extensive and current literature that identifies the repercussions on the foot when the subjects have been recipients of a kidney transplant. Despite this, there are articles that highlight the importance of identifying skin and nail conditions, as it helps reduce the association of the person's health status with morbidity and mortality [21], since in many cases these manifestations are generally secondary to immunosuppressive treatment [22].…”
Section: Discussionmentioning
confidence: 99%